2019
DOI: 10.1111/jcmm.14780
|View full text |Cite
|
Sign up to set email alerts
|

Effect of (R)‐salbutamol on the switch of phenotype and metabolic pattern in LPS‐induced macrophage cells

Abstract: Evidence demonstrates that M1 macrophage polarization promotes inflammatory disease. Here, we discovered that (R)‐salbutamol, a β2 receptor agonist, inhibits and reprograms the cellular metabolism of RAW264.7 macrophages. (R)‐salbutamol significantly inhibited LPS‐induced M1 macrophage polarization and downregulated expressions of typical M1 macrophage cytokines, including monocyte chemotactic protein‐1 (MCP‐1), interleukin‐1β (IL‐1β) and tumour necrosis factor α (TNF‐α). Also, (R)‐salbutamol significantly dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 55 publications
1
20
1
Order By: Relevance
“…So, we detected the bioenergetic profiles of mitochondrial respiration and aerobic glycolysis in LPS activated macrophages and compared with the cells pretreated with G-1. Our results showed that IFN-and LPS markedly altered cellular metabolism via switching OXPHOS to aerobic glycolysis, which was similar to other reports [22,30]. Meanwhile, we found G-1 significantly inhibited intracellular aerobic glycolysis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…So, we detected the bioenergetic profiles of mitochondrial respiration and aerobic glycolysis in LPS activated macrophages and compared with the cells pretreated with G-1. Our results showed that IFN-and LPS markedly altered cellular metabolism via switching OXPHOS to aerobic glycolysis, which was similar to other reports [22,30]. Meanwhile, we found G-1 significantly inhibited intracellular aerobic glycolysis.…”
Section: Discussionsupporting
confidence: 91%
“…The oxygen consumption rate (OCR) and extracellular acidification rate (ECAR) of the RAW 264.7 cells were detected using a Seahorse XF96 flux analyser (Agilent, California, USA) according to the method previously described [22,23]. 1×10 4 cells/well were seeded in XF 96 cell culture plate two days before the experiment.…”
Section: Seahorse Analysismentioning
confidence: 99%
“…Having established the differentiation protocol and confirmed an overall macrophage expression profile by RNAseq and flow cytometry, we next assessed whether the iPSC-derived macrophages faithfully recapitulate macrophage function. For this, we chose 16 compounds reported to modulate targets that are either affected by changes in cyclic adenosine monophosphate (cAMP) [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] or to have immune modulatory effects [ 41 , 42 , 43 , 44 , 45 , 46 ] ( Figure S6 ). These compounds were screened for modulatory effects on the phagocytosis of Zymosan particles ( Figure 5 ) and on cytokine release ( Figure 6 ) to demonstrate the applicability of iPSC-derived macrophages in small molecule screens with functional endpoints.…”
Section: Resultsmentioning
confidence: 99%
“…When glycogen is decomposed, a large amount of glucose 6-phosphate flows to the pentose phosphate pathway, which increases the ratio of NADPH/NADP + and promotes the production of GSH [143]. Blocking glycogen decomposition or inhibiting the oxidation stage of the pentose phosphate pathway will cause M 1 macrophages to reduce the GSH/GSSG ratio, increase ROS, and increase M 1 macrophages apoptosis [144,145]. Therefore, interfering with the flow of glycogen to PPP can promote the apoptosis of M1 macrophages mediated by ROS.…”
Section: Pentose Phosphate Pathwaymentioning
confidence: 99%